FOOD AND FEEDING OF LIZARD FISHES (SAURIDA SPP.) FROM NORTH WESTERN PART OF BAY OF BENGAL - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
The food and feeding of Saurida turnbil was studied with reference to sizeof fish, time (seasonal and diurnal), regions (latitude zones), sex and maturity.Though there was not much difference in the composition of the food in respect ofthe above factors, variations were however, 6bserved in the intensity of feeding.Fish formed the single major component